Kinetics of Isothermal Crystallization of Hydrogenated Castor Oil‐in‐Water Emulsions. (11th August 2013) - Yang, Dingzheng; Hrymak, Andrew N.; Kedzior, Stephanie
Abstract: Kinetics of isothermal crystallization of hydrogenated castor oil in water emulsions exhibiting multiple crystal morphologies have been studied experimentally by DSC and polarized light microscopy. The induction time of nucleation increases with the increase of the isothermal temperature under which crystallization occurred. Crystal growth has been observed by microscopy showing that both crystal morphologies, fibers and rosettes, grow linearly at the initial stage of crystallization and then slow down to reach a plateau value. The Avrami model, which has been widely used in kinetics studies of triacylglycerol systems, was employed to fit experimental results at different isothermal temperatures. It was found that experimental trends could be captured by introducing the volume fraction of each type of morphology into three‐dimensional and one‐dimensional full Avrami models.